Anterior Cruciate Ligament Mechanoreceptors and their Potential Importance in Remnant-Preserving Reconstruction: A Review of Basic Science and Clinical Findings - Kosy, Jonathan David; Mandalia, Vipul I. (The Journal of Knee Surgery, 2018)
Mechanoreceptors, within the anterior cruciate ligament (ACL), are believed to have importance in proprioception, contributing to dynamic knee stability. The potential for reinnervation of the ACL graft is one of the proposed advantages of remnant-preserving reconstruction. The aim of this review is to summarize advances in the basic science underpinning this function, alongside recent clinical studies, to define the current role for remnant-preservation.A comprehensive systematic review was performed using PubMed and Medline searches. Studies were analyzed with particular focus placed on the methodology used to either identify mechanoreceptors or test proprioception.Contemporary work, using immunohistological staining, has shown mechanoreceptors primarily within proximity to the bony attachments of the ACL (peripherally in the subsynovial layer). The number of these receptors has been shown to decrease rapidly, following rupture, with adhesion to the posterior cruciate ligament slowing this decline. Recent studies have shown proprioceptive deficits, in both the injured and contralateral knees, with the clinical relevance of findings limited by testing methodology and the small differences found. The advantages of remnant-preservation, seen primarily in animal studies, have not been shown in systematic reviews or meta-analysis of clinical studies.The potential for reinnervation of the graft is likely time-dependent and reliant on continued loading of the remnant. Therefore, current clinical use and future research should focus on preserving remnants within 6 months of injury that remain loaded by adherence to the posterior cruciate ligament. Subsequent testing should account for central neurological changes and focus on clinically relevant outcomes.
Keywords: mechanoreceptors; anterior cruciate ligament; anterior cruciate ligament reconstruction; remnant-preservation